Analysis Certification Teachers On Teacher Professional Education In Service - Sri Uchtiawati (Universitas Muhammadiyah Gresik, 2020)
The problem of this research is the need to improve the quality of Education, which in the analysis obtained by a base to enhance the quality of Education. Knowledge lies in the sub-system of teachers because basically, the teacher is learning agent. And how the efforts to upgrade the quality of Education is then, by invitation Act s item of national Education and law teacher and lecturer, is it relieved l formal that teachers must have a teaching certificate, or known as a teacher's certificate (sergu). The essence of teacher certification award